Warga Kerajaan di Dunia Asing: Menavigasi Ketegangan Teologis Antara Hukum Dunia dan Hukum Kerajaan Allah - Tedja Mahananie, Esa (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2025)
Christians live within an unavoidable existential tension between the demands of worldly law and the law of God's Kingdom. This article argues that this tension is not a problem to be eliminated, but rather the space in which authentic Christian discipleship occurs. Adopting a theological framework that synthesizes three main pillars, this study offers a path for navigating this dilemma. First, George Eldon Ladd's